Contextual Teaching and Learning Based on Ethnoscience in Natural and Social Sciences: Pengajaran dan Pembelajaran Kontekstual Berbasis Etnosains dalam Ilmu Alam dan Ilmu Sosial - Aprilia, Vindy; Sartika, Septi Budi; Salim, Agus (Indonesian Journal of Education Methods Development, 2025)
General Background: The integration of cultural contexts into education has gained increasing attention as a means to enhance relevance and engagement in learning. Specific Background: In Indonesia, the application of ethnoscience within the Contextual Teaching and Learning (CTL) approach has shown potential for improving students’ comprehension of integrated Science and Social Studies (IPAS) by linking concepts to local wisdom. Knowledge Gap: However, empirical evidence on the effectiveness of ethnoscience-based CTL for elementary-level IPAS learning remains limited. Aim: This study investigates the effectiveness of ethnoscience-based CTL in enhancing learning outcomes, engagement, and perceptions among fifth-grade students. Results: Conducted at SD Muhammadiyah 1 Sedati with 30 participants, the experimental one-group pretest–posttest design revealed that teacher performance and student activity were both rated “good,” learning outcomes improved significantly with an N-Gain of 70% (high category), and student responses were positive. Novelty: The study uniquely combines CTL and ethnoscience in IPAS learning, demonstrating how cultural integration strengthens conceptual understanding. Implications: These findings support the adoption of culturally grounded CTL approaches to foster active participation, improve achievement, and promote meaningful connections between academic content and students’ sociocultural environment. Highlights: Combines CTL with ethnoscience for IPAS learning. Achieves high N-Gain in student outcomes. Enhances engagement through cultural relevance. Keywords: Effectiveness, CTL Approach, Ethnoscience, Science Education, Student Engagement